Decubitus Ulcer Patients Profile in Department of Plastic Surgery Dr. Soetomo General Hospital Surabaya from January to December 2018 - Azmil Permatasari; Magda Rosalina Hutagalung; Nuniek Nugraheni Sulistiawaty; Agus Susanto Budi (Faculty of Medicine Universitas Airlangga, 2022)
Highlights:1. Decubitus ulcers can be caused by prolonged immobilization and constant pressure on the body.2. Decubitus ulcer patients were dominated by females, aged 46-65 years old, and the most common comorbidity history was patients with limb weakness. AbstractIntroduction: Continuous pressure on the area of the skin, especially in areas with bone protrusion can cause decubitus ulcers. Decubitus ulcers can occur to anyone, both children and adults, male or female, especially in people who experience daily immobility in a bed or wheelchair. Many treatments are performed in order to prevent decubitus ulcers to not becoming a more dangerous condition. This study aimed to determine the profile of pressure ulcers in Dr. Soetomo General Hospital Surabaya.Methods: This was a cross-sectional descriptive retrospective study. Secondary data were collected from 25 medical records of pressure ulcer patients in the Outpatient Clinic Department of Plastic Surgery Dr. Soetomo General Hospital Surabaya from January to December 2018. The data such as age, gender, risk factors, comorbidities history, and management were taken. The calculation was performed using Microsoft Excel.Results: The majority of patients with pressure sores at the Outpatient Clinic Department of Plastic Surgery Dr. Soetomo General Hospital Surabaya from January to December 2018 were dominated by female patients aged 46-65 years old (24%), with the most common risk factor being immobilization (96%). Patients’ history showed that most patients with decubitus ulcers suffered from a weakness in the limbs (13%). The most common treatment was wound bed preparation (46%) and education (46%).Conclusion: Pressure ulcers most often occurred in women aged 41-65 years or the elderly. Most patients experienced immobilization as a risk factor for pressure ulcers. These patients were dominated by those who had a history of illness with limb weakness. The therapy applied to patients with pressure sores was the preparation of wound beds and education to the patient.